THE STUDENTS’ EYESIGHTS TOWARDS THE USE OF GOOGLE CLASSROOM AS LANGUAGE LEARNING MEDIA (International Conference on Social and Islamic Studies, 2022)
Online learning has become a teaching method used to reduce the spread of Covid-19 during the pandemic. In the implementation of online learning, many online platforms are used. Google Classroom is one of them. This research focused on the students' perceptions on the use of Google classroom as language learning media. This research aimed to investigate the perceptions of second-year students on the use of Google Classroom as language learning media at SMAN 8 Gowa, South Sulawesi, Indonesia. The method of this research was a quantitative method with a survey research design. The population of this research was the second-year students of SMAN 8 Gowa, South Sulawesi, Indonesia. The purposive sampling technique was used as the technique in selecting the subject of this research. The subject of this research was 66 students from three classes who filled out the questionnaire. A questionnaire was used to collect the data. The data analysis technique used descriptive statistics by describing the frequency, and percentage of the data. The result indicated that many students accepted that Google Classroom is easy to use and accessible. It made the process of learning English easier and helps the students to develop self-directed learning attitudes. Therefore, it helps to facilitate teaching and learning and also saves time and effort in submitting tasks. In addition, Google Classroom does not consume a lot of internet data. However, Google Classroom is less effective in learning English at SMAN 8 Gowa, South Sulawesi, Indonesia. It was found that more than a half of students argued that Google Classroom makes the English learning process more effective and also denied that English skills are enhanced while using Google Classroom.